UNC13C Suppress Tumor Progression via Inhibiting EMT Pathway and Improves Survival in Oral Squamous Cell Carcinoma - Velmurugan, Bharath Kumar; Yeh, Kun-Tu; Hsieh, Ming-Ju; Yeh, Chung-Min; Lin, Chia-Chieh; Kao, Chuan-Yu; Huang, Lan-Ru; Lin, Shu-Hui (Frontiers in Oncology, 2019)
Potential function of UNC13C in variety of cancers including, oral squamous cell carcinoma (OSCC) remains obscure. In the present study, immunohistochemical staining in tissue microarrays containing 268 OSCC samples showed that UNC13C protein levels were inversely correlated with AJCC Stage III and IV (P=0.002) and death (P=0.0134). Patients with lower UNC13C expression had a significantly shorter survival (P=0.0231) than those with higher UNC13C expression. We also identified decreased overall UNC13C expression in oral cancer cell lines. In addition, our functional analysis of UNC13C shows that overexpression of UNC13C inhibited migration and invasion capacities of SCC-9 and SAS cells compared with the empty plasmid transfected cells. Further experiments suggested that transcription factors (Slug, Snail, Twist, ZEB1) and mesenchymal marker (Vimentin) were down regulated and Tight Junction Protein (Claudin1) was up regulated after UNC13C overexpression in SCC9 and SAS cells. The novel role of UNC13C is revealed for the first time in OSCC. In summary, these results suggest that UNC13C as a novel tumor suppressor and an essential regulator of EMT signaling pathway during OSCC progression, and thus it could be used as a target for preventing oral cancer metastasis.